2019
DOI: 10.1177/1558944719840737
|View full text |Cite
|
Sign up to set email alerts
|

The Pronator Quadratus Muscle After Volar Plating: Ultrasound Evaluation of Anatomical Changes Correlated to Patient-Reported Clinical Outcome

Abstract: Background: Repair of the pronator quadratus (PQ) muscle with sutures has been reported durable after volar plating of distal radius fractures (DRF). It is unclear how the muscle reacts if not repaired and if a retracted muscle correlates to worse functional outcome or complications. In this study, we use ultrasound to investigate the anatomy of the PQ muscle after volar plating with PQ repair or nonrepair and correlate the ultrasound findings with patient-reported outcome. Methods: Participants were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…It was previously believed that the PQ muscle was less critical, and that the anterior rotator function was limited; however, this is not the case. Jesper Sonntag et al [ 41 ] concluded in a study that with or without repair of the PQ muscle after incision, ultrasound results showed that both were shorter than the healthy side. Still, the shortening was more significant in the unrepaired group.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously believed that the PQ muscle was less critical, and that the anterior rotator function was limited; however, this is not the case. Jesper Sonntag et al [ 41 ] concluded in a study that with or without repair of the PQ muscle after incision, ultrasound results showed that both were shorter than the healthy side. Still, the shortening was more significant in the unrepaired group.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously believed that the PQ muscle was less critical, and that the anterior rotator function was limited; however, this is not the case. Jesper Sonntag et al [43] concluded in a study that with or without repair of the PQ muscle after incision, ultrasound results showed that both were shorter than the healthy side. Still, the shortening was more signi cant in the unrepaired group.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies showed statistically non-significant(p>0.05) increased manipulation success rate in the US assisted DRF reductions, [11,15,26]. Bozkurt et al, [40] showed a 97.5% success rate in US group but no number was available for the control arm. Esmailian et al, [41] showed a slightly lower rate of 94.2 % compared to 94.8% in the control group.…”
Section: Manipulation Success Ratementioning
confidence: 96%
“…USA, [15,30], Canada, [26,29], Japan, [11], Iran, [17,28] and Turkey, [40]. All studies included adult population except for two studies, [15,16] which also included children but did not give a separate data for them, with the age range of 3-95 years.…”
Section: Study Characteristicsmentioning
confidence: 99%